ANALISIS KINERJA KEUANGAN PADA BPRS NIAGA MADANI CABANG MAROS - Abdul Khalik (AkMen JURNAL ILMIAH, 2013)
This study aims to determine the financial performance of Bank Niaga SRB Maros Civil Branch and to determine the maximum financial contribution to the company in carrying out its activities in the SRB Commerce Branch Madani Maros. The results showed that the growth trend in the analysis for 3 (three) years showed that the SRB Bank Niaga branch Madani Maros its financial performance is still very good when viewed from the aspect of growth. In the ratio analysis method CAMEL SRB Bank Niaga Madani still very good, because it is still above the CAR set by Bank Indonesia at 8%, the higher the value of CAR, then the better capital. In the aspect of asset quality, Earning and liquidity aspects are still very good, just needs to be improved fundingya management, so that profits increased from year to year.